2022
DOI: 10.1021/acs.jctc.1c01295
|View full text |Cite
|
Sign up to set email alerts
|

Open-Shell Variant of the London Dispersion-Corrected Hartree–Fock Method (HFLD) for the Quantification and Analysis of Noncovalent Interaction Energies

Abstract: The London dispersion (LD)-corrected Hartree–Fock (HF) method (HFLD) is an ab initio approach for the quantification and analysis of noncovalent interactions (NCIs) in large systems that is based on the domain-based local pair natural orbital coupled-cluster (DLPNO-CC) theory. In the original HFLD paper, we discussed the implementation, accuracy, and efficiency of its closed-shell variant. Herein, an extension of this method to open-shell molecular systems is presented. Its accuracy is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 138 publications
0
11
0
Order By: Relevance
“… 21 , 22 In particular, the two-point CPS(6/7) extrapolation scheme 21 , 22 allows DLPNO-CCSD(T) relative energy calculations with sub-kJ/mol accuracy with respect to canonical CCSD(T). 21 24 It is worth mentioning here that other extrapolation approaches have been suggested for local correlation methods with varying degree of accuracy. 14 , 25 28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 , 22 In particular, the two-point CPS(6/7) extrapolation scheme 21 , 22 allows DLPNO-CCSD(T) relative energy calculations with sub-kJ/mol accuracy with respect to canonical CCSD(T). 21 24 It is worth mentioning here that other extrapolation approaches have been suggested for local correlation methods with varying degree of accuracy. 14 , 25 28 …”
Section: Introductionmentioning
confidence: 99%
“…However, for systems with a complex electronic structure, tighter T CutPNO values might be necessary, which necessarily reduces the efficiency of the methodology. As an alternative to tightening the T CutPNO threshold for approaching the complete PNO space (CPS) limit with a given atomic orbital basis set, extrapolation schemes that exploit the smooth dependence of the correlation energy on the T CutPNO parameter can be used. , In particular, the two-point CPS­(6/7) extrapolation scheme , allows DLPNO-CCSD­(T) relative energy calculations with sub-kJ/mol accuracy with respect to canonical CCSD­(T). It is worth mentioning here that other extrapolation approaches have been suggested for local correlation methods with varying degree of accuracy. , …”
Section: Introductionmentioning
confidence: 99%
“…Accurate quantum mechanical calculations at the HFLD* level , were carried out to estimate the magnitude of intermolecular LD interactions in the solid state. With a cluster model of 11 di-adamantyl COT monomers extracted from the experimental crystal structure (Figure b), we found that the LD energy between the central monomer and its neighbors amounts to −68.2 kcal mol –1 .…”
mentioning
confidence: 99%
“…2 shows the most stable conformers found from the sampling procedure for all the catalysts studied in this work. The corresponding dispersion interaction density (DID) 83,84 plots at the HFLD/Silver level 85 are also shown and provide a spatial analysis of the role played by London dispersion forces acting between the monomers.…”
Section: Resultsmentioning
confidence: 99%